Respuesta :

Answer:

1/6p - 4/5

Step-by-step explanation:

we combine like terms, so the numbers with p's are added together, and the regular numbers are added together too

we have to make -2/3 and 5/6 the same denominator, so multiply each number in -2/3 by two, giving you -4/6

-4/6p+5/6p=1/6p

simply do 1/5-1 which equals -4/5

put both solutions into one equation= 1/6p - 4/5

The simplified form of the expression -(2/3)p + 1/5 - 1 + (5/6)p will be (3/2)p - 4/5.

What is Algebra?

The analysis of mathematical representations is algebra, and the handling of those symbols is logic.

Making anything easier to accomplish or comprehend, as well as making it less difficult, is the definition of simplification.

The expression is given below.

⇒ -(2/3)p + 1/5 - 1 + (5/6)p

Simplify the equation, then we have

⇒ -(2/3)p + 1/5 - 1 + (5/6)p

⇒ (5/6)p - (2/3)p + 1/5 - 1

⇒ (5/6)p - (4/6)p + 1/5 - 1

⇒ (4 + 5/6)p + (1 - 5)/5

⇒ (9/6)p - 4/5

⇒ (3/2)p - 4/5

Thus, the simplified form of the expression -(2/3)p + 1/5 - 1 + (5/6)p will be (3/2)p - 4/5.

More about the Algebra link is given below.

https://brainly.com/question/953809

#SPJ2